Предмет: Математика, автор: Аноним

Вычислите значение выражения: 1) -3 1/12+ 1/6=
2) 3 6/7+(-6 4/9)=
3) 9 1/6+(- 5 3/4)=​

Ответы

Автор ответа: Аноним
4

1) - 3 \frac{1}{12}  +  \frac{1 {}^{(2} }{6}   =  -  \frac{37}{12}  +  \frac{2}{12}  =  -  \frac{35}{12}  =  - 2 \frac{11}{12} \\  \\ 2)3 \frac{6 {}^{(9} }{7}  + ( - 6 \frac{4 {}^{(7} }{9} ) = 3 \frac{54}{63}  + ( - 6 \frac{28}{63} ) =  \frac{243}{63}  + (  -  \frac{406}{63} ) =  \frac{243}{63}  -  \frac{406}{63}  =  -  \frac{163}{63}  =  - 2 \frac{37}{63}  \\  \\ 3)9 \frac{1 {}^{(4} }{6}  + ( - 5 \frac{3 {}^{(6} }{4} ) = 9 \frac{4}{24}  + ( - 5 \frac{18}{24} ) = 9 \frac{4}{24}  - 5 \frac{18}{24}  =  \frac{220}{24}  -  \frac{138}{24}  =  \frac{82}{24}  = 3 \frac{10}{24 }  = 3 \frac{5}{12}

Похожие вопросы
Предмет: Алгебра, автор: revoforeve